Is adjuvant radiotherapy necessary for FIGO stage 1a grade 2 endometrial endometrioid adenocarcinoma? - (:unkn) unknown (TURGUT YAYINCILIK & TICARET AS, 2015)
Objective: The impact of adjuvant radiotherapy on the rates of survival and local recurrence was analyzed in patients diagnosed with International Federation of Gynecology and Obstetrics (FIGO) stage 1a grade 2 endometrial endometrioid adenocarcinoma. Material and Methods: Medical records of 82 patients diagnosed and treated for FIGO stage 1a grade 2 endometrial endometrioid adenocarcinoma were reviewed retrospectively. A group of 59 patients who received postoperative radiotherapy was compared with a control group of 23 subjects treated without adjuvant radiotherapy; the duration of survival as well as the local recurrence and metastasis rates were evaluated in both groups. Results: The analysis of patient data has revealed the rate of local recurrence as 4.3% vs. 1.7% (p=0.485), the rate of distant metastasis as 4.3% vs. 6.9% (p=1.000), and the mean survival time as 83.6 +/- 38.7 vs. 81.5 +/- 37.5 months (p=0.828) in the adjuvant radiotherapy and control groups, respectively. Conclusion: In the presented study, adjuvant radiotherapy failed to improve the overall survival of the patients in the low-risk group (stage 1a grade 2). With the addition of the significant risk of radiation toxicity, it is highly probable that these patients will not benefit from postoperative radiotherapy. Close observation should be performed following the primary surgery in this patient group. Nevertheless, it should also be considered that adjuvant radiotherapy is a very effective treatment modality for the recovery of patients with vaginal relapse.
Keywords: Endometrial cancer; adjuvant radiotherapy; mean survival time; GYNECOLOGIC-ONCOLOGY-GROUP; RADIATION-THERAPY; PELVIC RADIATION; RANDOMIZED-TRIAL; CANCER; CARCINOMA; IRRADIATION; PATTERNS; SURGERY